Study of Housing Typology in Kauman, Parakan, Temanggung, Central Java - ARI WIDYATI PURWANTIASNING; SAEFUL BAHRI (Jurnal Koridor, 2025)
The study of housing typology in the residential area of the Kauman Parakan community is a research that contains a description of the typology of the typical housing of the Kauman Parakan community. The Kauman community is widespread in several parts of Java Island, one of which is in Temanggung Regency, precisely in Parakan District. The typology of the dwelling itself includes several aspects contained in a dwelling or residence, including spatial systems related to the plan, model systems related to appearance, and physical systems related to materials. The purpose of this study is to identify the distinctive elements found in the dwellings of the Kauman community, Parakan. The research method used is a qualitative-descriptive method, where data is taken from research directly by referring to related literature sources. Based on the results of the analysis that has been carried out, it can be concluded that the typology of housing in Kauman, Parakan is influenced by the daily activities of the owner and the number of users. Keyword: Architecture, Typology, Housing, Kauman, Parakan